Co-expression of neuropeptide Y Y1 and Y5 receptors results in heterodimerization and altered functional properties - Gehlert, Donald R.; Schober, Douglas A.; Morin, Michelle; Berglund, Magnus M. (Biochemical pharmacology, 2007)
Centrally administered neuropeptide Y (NPY) produces anxiolytic and orexigenic effects by interacting with Y1 and Y5 receptors that are colocalized in many brain regions. Therefore, we tested the hypothesis that co-expression of Y1 and Y5 receptors results in heterodimerization, altered pharmacological properties and altered desensitization. To accomplish this, the carboxyl-termini of Y1 and Y5 receptors were fused with Renilla luciferase and green flourescent protein and the proximity of the tagged receptors assessed using bioluminescent resonance energy transfer. Under basal conditions, cotransfection of tagged Y1 receptor and Y5 produced a substantial dimerization signal that was unaffected by the endogenous, nonselective agonists, NPY and peptide YY (PYY). Selective Y5 agonists produced an increase in the dimerization signal while Y5 antagonists also produced a slight but significant increase. In the absence of agonists, selective antagonists decreased dimerization. In functional studies, Y5 agonists produced a greater inhibition of adenylyl cyclase activity in Y1/Y5 cells than cells expressing Y5 alone while NPY and PYY exhibited no difference. With PYY stimulation, the Y1 antagonist became inactive and the Y5 antagonist exhibited uncompetitive kinetics in the Y1/Y5 cell line. In confocal microscopy studies, Y1/Y5 co-expression resulted in increased Y5 signaling following PYY stimulation. Addition of both Y1 and Y5 receptor antagonists was required to significantly decrease PYY-induced internalization. Therefore, Y1/Y5 co-expression results in heterodimerization, altered agonist and antagonist responses and reduced internalization rate. These results may account for the complex pharmacology observed when assessing the responses to NPY and analogs in vivo.